Samuel C. Phillips papers - Phillips, Samuel C. (Samuel Cochran), 1921-1990.
Correspondence, diaries, memoranda, reports, family and personal papers, photographs, and other papers documenting Phillips's career in the U.S. Air Force where he specialized in ballistics and weapons research; as director of Project Apollo, the lunar landing program of the U.S. National Aeronautics and Space Administration; and as an executive with TRW, Inc., and other defense contracting firms. Documents his work as commander of the Space and Missile Systems Organization and U.S. Air Force Systems Command. Includes material on atomic weapons tests, Minuteman intercontinental ballistic missile system, Project Saturn (rocket development), Strategic Defense Initiative, Superconducting Super Collider, Titan III launch system, and other defense and aeronautical projects with which he was involved during the Cold War and the space race between the United States and the Soviet Union. Correspondents include Grumman Aircraft Engineering Corporation and North American Aviation, inc.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Geography and Map Division.
Library of Congress Music Division.
U.S. Air Force officer, space agency official, intelligence agency director, and defense industry executive.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Phillips family; United States. -- Air Force; United States. -- Air Force. -- Systems Command; United States. -- National Aeronautics and Space Administration; Grumman Aircraft Engineering Corporation -- Correspondence; North American Aviation -- Correspondence; Project Apollo (U.S.); Saturn Project (U.S.); Space and Missile Systems Organization (U.S.); TRW Inc; Ballistic missile defenses; Ballistics; Ballistics -- Research; Cold War; Defense contracts -- United States; Defense industries -- United States; Intercontinental ballistic missiles; Launch vehicles (Astronautics); Military weapons; Military weapons -- Research; Minuteman (Missile); Nuclear arms control; Nuclear weapons -- Testing; Particle accelerators; Particles (Nuclear physics); Rockets (Aeronautics); Space flight to the moon; Space race -- Soviet Union; Space race -- United States; Strategic Defense Initiative; Superconducting Super Collider; Moon -- Exploration; Air Force officers; Executives; Public officials